Teaching Modeling Using the Total Physical Response (TPR) Technique as a Variation in Learning English at SDN Gampingrowo 02 Sidoarjo: English - Basuki, Edi Pujo; Aquariza, Novi Rahmania; Shari, Destita (New Language Dimensions, 2022)
This study aims to find out whether there was statistically significant difference of students’ English vocabulary achievement after the implementation of Total Physical Response (TPR) technique, the learning technique focuses on body movement and music. In addition, this research aims to find out how much influence the Total Physical Response (TPR) method has on learning English vocabulary that students can master it correctly during the process of teaching-learning activities. This research was a quantitative-qualitative research design. The subject of this research were 20 students of SDN Gampingrowo 02, Tarik, Sidoarjo. The English vocabulary tests and observation sheets were used to collect the data as the instrument of this study. This data was analyzed using the Paired Sample T-Test. The result of this study showed that there was significant difference of students’ English vocabulary achievement after the implementation of Total Physical Response (TPR) technique in the application of English vocabulary learning, with p=0.00>0.005. This suggests that Total Physical Response (TPR) technique can help the students to understand English vocabulary easily and more interestingly. Keywords: Vocabulary, Total Physical Response method, teaching vocabulary, English learning